Chokepoints in global food trade: Assessing the risk. (December 2017) - Wellesley, Laura; Preston, Felix; Lehne, Johanna; Bailey, Rob
Abstract: The global disaggregation of food supply chains and just-in-time business models with low inventories mean that governments, traders, producers and consumers are increasingly exposed to unforeseen interruptions to supply and associated volatility in food prices. While considerable research has examined the risk of disturbance in global energy markets resulting from a disruption to physical chokepoints along major trade routes, no comparable analysis has been undertaken for agricultural commodities. Here we present the Chatham House Maritime Analysis Tool (CH-MAT), which estimates the volume and value of staple foods passing through maritime chokepoints. The CH-MAT permits analysis of flows through chokepoints arising from bilateral trade in commodities over the period 2000 to 2015. The value of the CH-MAT is illustrated by a first assessment of global flows via maritime chokepoints. We discuss how such data can be combined with information on inland and overland transport networks, strategic reserves and environmental change, to enhance understanding of the risks associated with disruption to critical infrastructure – owing to weather events, trade restrictions, conflict, congestion, or institutional failures. We consider the applications within risk management frameworks, and governance mechanisms at national, and multilateral level and identify priority measures to enhance global food security.